SHELF LIFE STABILITY OF OSMODEHYDRATED WHITE CABBAGE - MATHEMATICAL MODEL - Cvetković, Biljana (Journal on Processing and Energy in Agriculture, 2021)
The aim of the present work is to deternmine the shelf life of osmodehydrated white cabbage in three different osmotic solutions. Chemical and color parameters were analysed so as the sensory acceptance and microbiological profile of the OT cabbage after 90 days of storage. Hybrid “Bravo“ was considered within this research because if its high yield and wide cultivation in province of Vojvodina. Solutions of sucrose and chloride was applied so as sugar beet molasses in OT. OT cabbage was packed in MAP with variation in gas mixture of 40:60/ CO2:N2 (atmosphere 1) and 80:20/CO2:N2 (atmosphere 2). Shelf-life evaluation is shown good sensorial acceptance, satisfied microbiological quality. The obtained mathematical model was able to successfully predict experimental results. The model is easy to implement could be effectively used for predictive purposes, modelling and optimization of the osmotic treatment.